Absorption of Fluorinated Greenhouse Gases Using Fluorinated Ionic Liquids - Sosa, Julio E. (2022)
funding of the KET4F-Gas project, SOE2/P1/P0823, co -funded by the Interreg Sudoe Programme through the European Regional Development Fund (ERDF). FCT/MCTES for financial support through IF/00190/2014 , IF/00210/2014 financial support through the Norma TransitOria DL 57/2016 Program Contract (FCT/MCTES). FCT/MCTES (UID/QUI/50006/2019).